The influence of work-family conflict factors on employees' job satisfaction - Miker, Anak Kuyu@Denis. (Universiti Malaysia Sarawak (UNIMAS), 2011)
The aim of this study is to identify the influence of work-family conflict among the employee. The factors concerned are role overload, work-to-family conflict (WFC), family-to-work conflict (FWC) and caregiver strain. Besides, this study also aims to investigate the dominant factor that influences employees' job satisfaction among the employees. A quantitative survey approach by using questionnaires had been carried out as instrument for data collection. 130 sets of questionnaires were distributed to the employees at SESCO and Jabatan Tanah dan Survei Sri Aman. However, only 78 sets of valid questionnaires were being returned and used for the analysis. Pearson Correlation "r" had been used to identify the relationship between the variables while Multiple Regression Linear was used to identify dominant factor that influences employees' job satisfaction. The finding reveals that job satisfaction among the employees is in the average level and there are significant relationships between the independent variables and the dependent variables. Furthermore, work-tofamily conflict is identified as the dominant factor that influences employees' job satisfaction. Thus, it is recommended that the organization and management should enhance the organizational policies related to work-family conflict and the skill of supervisors and managers to play effective key roles in increasing employees' job satisfaction.